Echocardiographic estimation of left ventricular‐arterial coupling in dogs with myxomatous mitral valve disease - Osuga, Tatsuyuki (J Vet Intern Med, 2021)
BACKGROUND: The effective arterial elastance (Ea) to left ventricular (LV) end‐systolic elastance (Ees) ratio (Ea/Ees) is an index of the interaction between LV and systemic arterial systems, left ventricular‐arterial coupling (VAC). The Ea is an index of total arterial load of the LV, whereas Ees is an index of LV systolic function. In humans, inappropriate VAC based on increased Ea/Ees estimated using echocardiography is associated with more advanced heart disease severity. HYPOTHESIS: Left ventricular‐arterial coupling assessed by echocardiographic estimation of Ea/Ees is associated with disease severity in dogs with myxomatous mitral valve disease (MMVD). ANIMALS: Ninety MMVD dogs and 61 healthy dogs. METHODS: Prospective cross‐sectional study. The MMVD dogs were classified into stages B1, B2, or C according to American College of Veterinary Internal Medicine guidelines. Effective arterial elastance was echocardiographically estimated using the formula: mean blood pressure/(forward stroke volume/body weight). End‐systolic elastance was echocardiographically estimated using the formula: mean blood pressure/(LV end‐systolic volume/body weight). The ratio Ea/Ees was calculated. RESULTS: The ratio Ea/Ees was higher in stage B2 dogs than in healthy dogs and dogs stage B1 (both P < .0001), and higher in stage C dogs than in healthy dogs and dogs in the other 2 stages (healthy vs C and B1 vs C, P < .0001; B2 vs C, P = .0005). Multivariable logistic regression analysis showed that Ea/Ees and the peak velocity of early diastolic transmitral flow to isovolumic relaxation time ratio were independent predictors of stage C among echocardiographic indices in MMVD dogs. CONCLUSIONS AND CLINICAL IMPORTANCE: Inappropriate VAC assessed by echocardiographically estimated Ea/Ees is associated with advanced disease severity in dogs with MMVD.